2010
DOI: 10.1002/jbmr.181
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole-body vibration training and vitamin D supplementation on muscle strength, muscle mass, and bone density in institutionalized elderly women: A 6-month randomized, controlled trial

Abstract: Sarcopenia and osteoporosis represent a growing public health problem. We studied the potential benefit of whole-body vibration (WBV) training given a conventional or a high dose of daily vitamin D supplementation in improving strength, muscle mass, and bone density in postmenopausal women. In a 2 Â 2 factorial-design trial, 113 institutionalized elderly females aged over 70 years (mean age 79.6 years) were randomly assigned either to a WBV or a no-training group, receiving either a conventional dose (880 IU/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 48 publications
2
104
0
13
Order By: Relevance
“…(16) In another study of 710 post-menopausal women, using low-magnitude high-frequency vibration (LMHFV) for 18 months, the author stated that the BMD of the hip and spine showed a positive trend in the vibration group compared to the controls (mean between-group difference 1.43% for femoral neck, 1.12% for spine) (22). The author concluded that the effect was not statistically significant after Bonferroni adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…(16) In another study of 710 post-menopausal women, using low-magnitude high-frequency vibration (LMHFV) for 18 months, the author stated that the BMD of the hip and spine showed a positive trend in the vibration group compared to the controls (mean between-group difference 1.43% for femoral neck, 1.12% for spine) (22). The author concluded that the effect was not statistically significant after Bonferroni adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most recent research of Gómez-Cabello et al (27) did not confirm the beneficial effects of WBV on the anabolic activity of bone tissue. Verschueren et al (68), on the other hand, found a significant 0.75% increase in total-hip BMD while Lai et al (36) noted a 2.032% increase in lumbar BMD after a WBV program. It has been emphasized, however, that a similar effect was obtained in women with vitamin D supplementation (68) or balance training (62).…”
Section: Geriatricsmentioning
confidence: 95%
“…The density of the hip bone (68), lumbar spine (36), or the tibia (62) was assessed with dual-energy X-ray absorptiometry and/or peripheral quantitative computed tomography (36,62,68). There were several differences between training programs: both vertical (66) and side-alternating WBV (62) were used; training duration ranged from 11 weeks (27) to 9 months (62); uniform vibration parameters were applied (66) or, if needed, changed according to overload principle (62,68). Study participants most often performed static and/or dynamic exercises, including squats and standing (27,62,68).…”
Section: Geriatricsmentioning
confidence: 99%
See 1 more Smart Citation
“…En adultos sanos la suplementación con Vitamina D no previene Osteoporosis, pero en los ancianos mantener adecuadas reservas de vitamina D combinado con ingesta sufi ciente de calcio es una efectiva estrategia para prevenir fracturas de cadera. (290)(291)(292)(293)(294)(295)(296)(297)(298)(299)(300).…”
Section: Calcio Y Riesgo Cardiovascularunclassified